A financial systemic stress index for Romania - Andreea Draghia; Sorina Emanuela Ștefoni (Financial Studies, 2020)
Detecting and measuring financial stress and its systemic risk channels have been one of the main concerns for authorities and financial supervisors especially after the financial crisis from 2008. In this paper, we aim to build a financial stress index (FSI) for Romania using monthly data from May 2005 to December 2019. The purpose of the indicator is to provide a quick, clear and intuitive assessment of the current state of the financial system. To do so, we compose 5 different sub-indexes using 9 variables which represent five different market segments: banking sector, money market, stock market, securities market and foreign exchange market. The results suggest that the financial stress index developed successfully captures the stress episodes observed in Romania in the past.
Keywords: E44; E58; G10; G20; 330; financial stress index; financial crisis; composite indicator of systemic stress